EFFECTIVE IMPLEMENTATION OF QUALITY MONITORING TOOLS: SOME REFLECTIONS - SINGH, POOJA; KUMAR, RAVI (THE PRIMARY TEACHER, 2013)
Sarva Shiksha Abhiyan (SSA) is implemented as India’s main programme for universalisation of elementary education. SSA makes an effort to universalise access to and retention in schools, while at the same time, emphasises quality of elementary education through community-based monitoring system. • What is Monitoring: Continuous assessment of progress for diagnosing strengths and weaknesses • Why it is Done: To take timely corrective measures for optimising effectiveness and quality • How it is Done: Identification of in-built milestones in programme, permeate through all its operations and components • When it is Done: Total life-cycle of programme – pre-planning stage to implementation of planning and assimilation. Government of India’s commitment for quality monitoring is also highlighted in the following paragraph from National Policy of Education (1986)–“Within a multi-level framework of educational development, central, state and district and local level agencies will participate in planning, coordination, monitoring and evaluation and monitoring implementation of National Policy on Education (1986).”